Efektivitas Pemberian KIE Pada Ibu Hamil Trimester III Terhadap Pemasangan Kontrasepsi IUD - Novi Heryani; Tetin Rismayanti (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Background: The use of IUD Contraception (Intra Uterin Device) is still very low due to low public knowledge about the advantages of the IUD Contraception method, so an increase in CIE (communication, information, and education) is carried out. Objective: This study aims to see whether there is an effect of giving CIE to pregnant women in the third trimester on the participation in the use of IUD contraceptives.Methods: The type of research is True Experiment with Pretest-Posttest With Control Group design on 25 respondents of third trimester pregnant women who are divided into treatment groups (25 respondents) and control groups (25 respondents).Result: The results showed that the provision of CIE (communication, information, and education) increased knowledge seen in the average pre-test treatment group, which was 52.68%, while in the post-test treatment group it was 72.08% with p value = 0.000, there was a significant increase in knowledge in the group. post-test and on the use of IUD Contraception with p value = 0.000 there is an effect of communication, information, and education on the participation in the use of IUD Contraception.Conclusions: The conclusion is that there is an increase in the level of knowledge in the treatment sample who is given Communication, Information, and Education and there is an effect of Family Planning Communication, Information, and Education on participation in IUD Contraception use